Pengaruh Aktivitas Kendaraan Pabrik Semen Terhadap Kinerja Jalan Lintas Sumatera - Wirawan, Febrian Andrey; Herianto, Dwi; Purba, Alekasnder (Universitas Lampung, 2018)
AbstractTrans Sumatera highway is an arterial road that connected Lampung in eastern and Aceh in western of Sumatera island. One of the road section passed in Lampung Selatan Regency, Lampung Province is Rangai Tri Tunggal district which is located in industrial zone. Througt traffic and local traffic are mix in this area and affecting road performance in terms of delay, conflict, degree of saturation. Hence, it is necessary to conduct such analysis in order to predict the level of services of Sumatra highway along the industrial area’s affected. The aim of this study is to analyze the influence of cement plant activities on the performance of Sumatera Highway. Data collected on Thursday and Saturday from 06:00 am to 06.00 pm (24-08-2017 and 26-08-2017). Calculation methods used are based on inter-urban roads category and unsignalised intersection which refers to MKJI 1997 and KM No. 14 of 2006. Based on findings the degree of saturations is ranging from 0.68 to 0.67 on Thursday and 0.68 to 0.66 on Saturdays indicating road performance at service level B stable and average speed of light vehicles is 41.5 km/h. Degree of saturation at the unsignalised intersection ranging from 0.97 to 0.96 on Thurday and Saturday and the delay is stand from 18sec/pcu to 17 sec/pcu on Thurday and Saturday which indicate service level C which mean as normal conditions. Keywords: degree of saturation, level of service, road performance.